Impact of Hydrocyclone Geometry on Glycerol Separation Efficiency in Biodiesel Purification - Warissara Trisap; Songtham Photaworn; Parinya Khongprom (International Journal of Chemical Engineering)
In the process of biodiesel production, a significant amount of glycerol, a by-product, is generated. This glycerol needs to be removed to purify biodiesel. Hydrocyclones have been developed for the efficient separation of immiscible liquid–liquid systems. However, the performance of hydrocyclones operating with high levels of liquid impurities requires further investigation. This research aims to examine the impact of hydrocyclone geometry on the efficiency of glycerol separation from biodiesel. Two types of hydrocyclones, short-tail and long-tail, were studied. A computational fluid dynamics (CFD) model, based on the Eulerian–Eulerian two-fluid model was used to predict the flow behavior within the system. Detailed hydrodynamic behavior in both short-tail and long-tail hydrocyclones was analyzed. Separation efficiency and biodiesel purity increased with a decrease in the glycerol volume fraction in the feed, an increase in inlet velocity, or an increase in glycerol density. However, these operating conditions had a minimal effect on the flow ratio. The short-tail hydrocyclone exhibited higher separation efficiency and biodiesel purity compared to the long-tail hydrocyclone, although its flow ratio was considerably lower. Therefore, the effect of long-tail hydrocyclone geometry on biodiesel purification was further investigated. It was found that separation efficiency and biodiesel purity improved with an increase in the underflow outlet diameter or a decrease in the overflow outlet diameter. However, these changes had the opposite effect on the flow ratio. Additionally, the optimum configuration of the long-tail hydrocyclone was obtained.